Enterotoxin Profiling and Antibiogram of Escherichia coli Isolated from Poultry Feces in Dhaka District of Bangladesh - Bashar, Tanvir; Rahman, Mostafizur; Rabbi, Fazle Alam; Noor, Rashed; Rahman, M Majibur (Stamford Journal of Microbiology, 2011)
Bacterial diseases remain a threat to the poultry industry and countermeasures to prevent and control them are needed to prevent production losses. With the continued threat of exotic and emerging diseases and the problem of the use of antibiotics in animal production, there is a serious and urgent need to find safe and practical alternatives to prevent or control pathogens. That,s why, our research has addressed in different poultry farms for detection of toxigenic Escherichia coli from poultry chicken feces adjacent to the Dhaka city, during the period of January 2009 to June 2009 and characterize their ability to produce enterotoxin and also examined the antibiogram of the isolates. A total of 60 fecal samples were collected and E. coli were isolated and identified by conventional cultural, biochemical and motility test.The heatstable toxins were determined by Suckling Mice Assay (SMA). The overall prevalence of E. coli was 100%. Among the isolates of E. coli, only 45% and 14% isolates showed β hemolysis and α hemolysis, respectively. Congo red binding has been used as a potential virulence marker and 69 % E. coli isolates in the present study showed congo red binder, among which, 59% isolates were hemolytic. A total of 20% and 5% isolates showed the presence of LT and ST enterotoxin in their guts by Suckling Mice assay, respectively. The antibiotic sensitivity pattern shown that the isolates were highly sensitive (100%) to imipenem, pipercillin, neomycin and ceftrixone. Results from this study revealed the high prevalence rate of E. coli isolates with variable resistance against a wide range of antimicrobial drug. It may suggest that the high resistance of E. coli to antibiotics as well as their toxigenic nature constitutes a threat not only to poultry industry of Bangladesh but also possesses a serious threat to public and animal health. DOI: http://dx.doi.org/10.3329/sjm.v1i1.9134 Stamford Journal of Microbiology, Vol.1(1), July 2011, p.51-57